AlN/GaN/AlN double heterostructures with thin AlN top barriers - Ch. Zervos; A. Bairamis; A. Adikimenakis; A. Kostopoulos; M. Kayambaki; K. Tsagaraki; G. Konstantinidis; A. Georgakilas (The Tenth International Conference on Advanced Semiconductor Devices and Microsystems, 2014)
Background Whether adding a bilateral superficial cervical plexus block to a thyroidectomy enhanced recovery pathway improves postoperative quality of recovery remains uncertain. Methods In a single-center prospective, randomized, double-blind, placebo-controlled trial in adults undergoing thyroidectomy with general anesthesia, participants were randomized to bilateral superficial cervical plexus blocks with 0.25% bupivacaine or saline. All participants received multimodal analgesia with dexamethasone, acetaminophen, nonsteroidal anti-inflammatory drugs, and incisional local anesthetic. The primary outcome was quality of recovery, measured by the QoR-40 survey, on postoperative day 1. Secondary outcomes included the need for rescue opioid, total opioid consumption, nausea, vomiting, antiemetic administration, length of stay in the postanesthesia care unit (PACU), and opioid use on postoperative day 1. Results A total of 160 participants were randomized to receive a superficial cervical plexus block with bupivacaine 0.25% (n = 78) or saline (n = 82). On postoperative day 1, mean QoR-40 scores were 174 (95% CI, 170 to 178) for bupivacaine and 173 (95% CI, 169 to 177) for saline. The adjusted mean difference between bupivacaine versus saline was 0.91 (95% CI, -3.57 to 5.40; P = 0.688). There were no significant between-group differences in the need for opioids in the PACU or on postoperative day 1, nausea, vomiting, or PACU length of stay. However, the total amount of opioid administered in the PACU was lower in the bupivacaine group (median [interquartile range], 0 [0 to 8]) compared with the saline group (2 [0 to 20]; Hodges-Lehmann location shift, 0 morphine milligram equivalents; 95% CI, -4 to 0; P = 0.017), and fewer participants in the bupivacaine group received rescue antiemetics (3 [3.8%] vs . 13 [16%]; difference, -12%; 95% CI, -22% to -1.8%; P = 0.011). Conclusions Bilateral superficial cervical plexus blocks did not improve quality of recovery after thyroidectomy when added to a multimodal analgesic regimen including dexamethasone, acetaminophen, nonsteroidal anti-inflammatory drugs, and incisional local anesthetic but were associated with lower total PACU opioid consumption.